PENGARUH HARGA, PRODUK DAN PROMOSI TERHADAP LOYALITAS KONSUMEN BIG JAY FAMILY KARAOKE - Rotinsulu, Eric; Sumayku, Sontje; Sambul, Sofia (Sam Ratulangi University, 2015)
Abstract. This study aims to determine the effect of price, product, and promotion of the Consumer Loyalty. Data were obtained through interviews with the owners of the company and distributing questionnaires to 60 consumers. This study uses multiple linear regression analysis approach. The results showed Price, Product, and Promotion jointly affect the Consumer Loyalty. However, prices partially greater influence on Consumer Loyalty compared with the Product and Promotion. Therefore, to increase customer loyalty Big Jay Family Karaoke, it is necessary to implement appropriate marketing strategies according to customer requirements. Keywords: Price, Product, Promotion, Consumer Loyalty.